Notary's Responsibility for The Occurrence of Identity Forgery in The Making of Authentic Deeds (Demak District Court Decision Study No.143/Pid.B/2023/PN Dmk) - Shaifuddin, Muhammad; Taufiq, Muhammad (TABELLIUS: Journal of Law, 2025)
Abstract. Currently the number of Notaries in Indonesia is increasing and making Notaries only focus on the large number of deeds made every day, so this creates a legal loophole, namely that the parties can use fake identities. This study aims to determine the responsibility of Notaries in the event of and legal protection for Notaries if there is falsification of identity carried out by the party in making authentic deeds with a case study on the Decision of the Demak District Court Number Decision 143 / Pid.B / 2023 / PN Dmk. This research method uses a normative legal approach, meaning that the research is conducted using a literature study approach and a statute approach. The type of data uses secondary data obtained from a literature study. The analysis in this study is prescriptive. The results of the study show that a Notary's deed whose face is using a false identity cannot be treated as an authentic deed. Regarding legal protection for Notaries, this can be done by adding a clause at the end of the deed stating that the Notary is not responsible for the false data of the face.Keywords: Authentic Deed; Criminal Investigation; Right of Refusal; Notary.